PENERAPAN IDENTIFIKASI, ASSESSMEN DAN PEMBELAJARAN PADA ANAK AUTIS DI SEKOLAH DASAR INKLUSIF - H. Ahmad Sofyan; Imam Yowono (Department of Special Education, 2014)
Implementation of the identification, assessment and learning in inclusive education in South Kalimantan still have constraints experienced. The lack of teacher’s knowledge and absence of guidelines for implementation of identification becomes crucial reason. The method used in this research is qualitative descriptive method. Subject in this research is one teacher and one school principal of Banua Hanyar 8 Banjarmasin that there are children with autism.. The findings of the research (1) how to identify children with autism at SD Banua Hanyar 8 using an instrument developed by DSM IV, the identification is done by teachers to identify children with autism (2) teacher assessment is understood to take the decision in making the learning program. That is done by the teacher in a way children collect data, and then analyzed to be taken into consideration together a program of learning (3) in the learning of children with autism teachers are required to modify the curriculum according to the needs of children with autism (4) constraints experienced by teachers in the identification and assessment of teacher’s understanding of them is not adequate, inclusive education is merely accepts children with special needs. Advice for teachers to continually identify and assessment to design programs and schools are expected to collaborate with experts to conduct trainingPenerapan identifikasi, penilaian dan pembelajaran di pendidikan inklusif di Kalimantan Selatan masih memiliki kendala yang dialami. Kurangnya pengetahuan guru dan tidak adanya pedoman pelaksanaan identifikasi menjadi alasan penting. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Subyek dalam penelitian ini adalah salah satu guru dan satu kepala sekolah dari Banua Hanyar 8 Banjarmasin dimana terdapat anak autis disekolahan tersebut .. Temuan penelitian (1) bagaimana mengidentifikasi anak autis di SD Banua Hanyar 8 menggunakan instrumen yang dikembangkan oleh DSM IV , identifikasi yang dilakukan oleh guru untuk mengidentifikasi anak-anak yang autis (2) penilaian guru dipahami untuk mengambil keputusan dalam membuat program pembelajaran. Itu dilakukan oleh guru dengan cara mengumpulkan data dari anak-anak dan kemudian dianalisis untuk dipertimbangkan bersama-sama program pembelajaran (3) dalam pembelajaran dengan anak autis, guru dituntut untuk memodifikasi kurikulum sesuai dengan kebutuhan anak-anak autis (4) kendala yang dialami oleh guru dalam mengindentifikasi dan penilaian memahami guru tidak memadai, pendidikan inklusif hanya menerima anak-anak dengan kebutuhan khusus. Saran bagi guru untuk terus mengidentifikasi dan penilaian untuk merancang program dan sekolah diharapkan untuk berkolaborasi dengan para ahli untuk melakukan pelatihan